A combination treatment of IFN-α2b and IFN-γ accelerates viral clearance and control inflammatory response in COVID-19: Preliminary results of a randomized controlled trial - Esquivel-Moynelo Idelsis; Pérez-Escribano Jésus; Duncan-Roberts Yaquelin; Vázquez-Blomquist Dania; Bequet-Romero Mónica; Báez-Rodríguez Lisandra; Castro-Ríos Jésus; Cobas-Cervantes Lisbeth; Pagé-Calvet Ernesto; Travieso-Pérez Saily; Martinez-Suarez Claudia; Campa-Legra Ivan; et al. (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2021)
Background: There is in vitro evidence that a combination of IFN-α and IFN-γ acts synergistically to inhibit SARS-CoV replication. We conducted a randomized controlled clinical trial to evaluate the safety and therapeutic efficacy of administration of a combination of IFN-α and IFN-γ for COVID-19. Methods: Adults with confirmed COVID-19 were randomized to receive either subcutaneous treatment with 3.0 MIU IFN-α2b and 0.5 MIU IFN-γ (study group), twice a week for two weeks, or an intramuscular injection of 3.0 MIU IFN-α2b (control group), three times a week for two weeks. Additionally, all patients received lopinavir-ritonavir (200/50 mg orally twice daily) and chloroquine (250 mg orally twice daily). The primary endpoints were time to viral clearance and the progression to severe COVID-19. The protocol was approved by the Ethics Committee from the Hospital and National Regulatory Agency. Informed consent was obtained from each participant. Results: A total of 79 patients with laboratory-confirmed SARS-CoV-2 infection, including symptomatic and asymptomatic cases, met the inclusion criteria, consented to participate in the trial and underwent randomization. 30 subjects were assessed in the study group and 33 in the control group. 23 (78.6%) in study group cleared virus after 4 days of treatment versus 13 (40.6%) in the control group (p=0.004). A significant difference in average time to viral clearance (p=0.0027) was detected in favor of the study group (3.0 days). We observed direct and significant correlations between time to viral clearance and the level of circulating lymphocytes, and a significant reduction in inflammatory parameters. Worsening of symptoms was detected in 6.6% and 3.3% of patients in the study and control groups, respectively. None of the subjects in either group progressed to severe COVID-19. All patients in both cohorts recovered. Adverse events were identified in 31.5% of patients, 28.5% in the control group, and 34.4% in the study group. Conclusions: A combination treatment of IFN-α2b plus IFN-γ in COVID-19 cases accelerated viral clearance and control inflammatory response compared with treatment with IFN-α2b alone. None of the patients progressed to severe COVID-19. The early application of HeberFERON can protect the patients to enter in a more severe disease. Trial registration: The study was registered on April 2020 at: registroclinico.sld.cu/en/trials/RPCEC00000307.